Karakteristik Tegangan Tembus AC Campuran Minyak Jagung Dan Minyak Mineral Sebagai Pertimbangan Alternatif Isolasi Cair - Panjaitan, Handerson; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This paper discusses the use of corn oil and mixing of vegetable oils with mineral oil (shell diala S4 ZX-I) to be used as an alternative material of liquid insulation. Vegetable oil samples used are corn oil before water content reduction, corn oil after water content reduction, and methyl esters. The focus of the study was to examine the characteristics of the mean breakdown voltage in a sample 100% pure vegetable oil and the mixing sample which was then compared with the results of the mean breakdown voltage test on a 100% pure mineral oil sample and according to IEC standard: 156 - 1995 & IEC : 6056 - 1995. The amount of comparison used between the two samples, ie 25% vegetable oil : 75% mineral oil, 50% vegetable oil : 50% mineral oil, and 75% vegetable oil : 25% mineral oil. The test results show the mean value of average breakdown voltage on the 100% sample of pure corn oil before a reduction in water content, 100% pure corn oil after water content reduction, 100% pure methyl ester, and 100% pure mineral oil are: 18.6 kV/2.5 mm, 35.7 kV/2.5 mm, 34.8 kV/2.5 mm, and 34.1 kV/2.5 mm. From the test, it is seen that 100% pure corn oil before the reduction of water content has not fullfilled the IEC standard: 156 1995 & IEC: 6056 - 1995. Meanwhile for a sample of corn oil mixture before reduction of water content with mineral oil and corn oil mixture after reduction of water content with mineral oil also have not fulfilled the standard of IEC: 156 -1995 & IEC: 60156 – 1995, while for some samples the mixture of methyl ester with mineral oil have fulfilled IEC standard: 156 1995 & IEC: 60156 - 1995. The addition of vegetable oil into mineral oil can also increase water contaminants and viscosity in oil mixed samples. The highest water contaminant and viscosity in each oil mixed sample are in the ratio of 75% vegetable oil : 25% mineral oil.Keywords: vegetables oil mixture, corn oil, metyl ester, oil insulation, breakdown voltage.